A ver el mundo nos vamos! - Brown, Margaret Wise, 1910-1952.; Tappin, Christine; Plana Castillon, Rosa. (Bath, UK : Parragon, 2012)
It's time to travel the world! Sing, dance, and play with children of other cultures.
Keywords: Travel -- Juvenile fiction; Multiculturalism -- Juvenile fiction; Viaje -- Novela juvenil